Distortions to current-voltage curves of CIGS cells with sputtered Zn(O,S) buffer layers - Song, Tao, author; Sites, James R., advisor; Wu, Mingzhong, committee member; Sampath, Walajabad, committee member (Colorado State University. Libraries, 2013)
Sputtered-deposited Zn(O,S) is an attractive alternative to CdS for Cu(In,Ga)Se2 (CIGS) thin-film solar cells' buffer layer. It has a higher band gap and thus allows greater blue photon collection to achieve higher photon current. The primary goal of the thesis is to investigate the effects of the secondary barrier at the buffer-absorber interface on the distortions to current-voltage (J-V) curves of sputtered-Zn(O,S)/CIGS solar cells. A straightforward photodiode model is employed in the numerical simulation to explain the physical mechanisms of the experimental J-V distortions including J-V crossover and red kink. It is shown that the secondary barrier is influenced by both the internal material properties, such as the conduction-band offset (CBO) and the doping density of Zn(O,S), and the external conditions, such as the light intensity and operating temperature. A key parameter for the sputter deposition of Zn(O,S) has been the oxygen fraction in the argon beam. It is found that the CBO varies with the oxygen fraction in the argon beam at a fixed temperature. With a greater CBO (∆EC > 0.3 eV), the resulting energy barrier limits the electron current flowing across the interface and thus leads to the J-V distortion. Two different ZnS targets, non-indium and indium-doped one, were used to deposit the Zn(O,S) buffer layer. At the same oxygen fraction in argon beam, a non-In-doped Zn(O,S) buffer with a smaller amount of doping forms a greater secondary barrier to limit the electron current due to the compensation of the Zn(O,S) buffer layer. In addition, the temperature-dependent J-V crossover can be explained by the temperature-dependent impact of the secondary barrier - at lower temperature in the dark, the maximum distortion-free barrier is reduced and results in a more serious current limitation, indicating a greater J-V crossover. It is also found that, under low-intensity illumination, there is a lower doping density of Zn(O,S) due to a smaller amount of photons with hν > Eg(Zn(O,S)) which can excite the buffer layer to release the trapped electrons from the deep-level defect state. The result is a greater secondary barrier to limit the electron current through the interface and shift the light J-V curve right towards the dark J-V curve at high bias (V > VOC) which reduces the J-V crossover. Finally, the quantitative comparison of J-V distortion between simulation and experiment is employed to examine the credibility of the secondary barrier theory.
Keywords: CIGS; Zn(O,S); solar cells; current-voltage distortion